1995
DOI: 10.1113/jphysiol.1995.sp020724
|View full text |Cite
|
Sign up to set email alerts
|

Localization of chemosensitive structures in the isolated brainstem of adult guinea‐pig.

Abstract: amplitude with no effect on respiratory burst frequency. 5. Bath superfusion with hypercapnic non-acidic Krebs solution increased the inspiratory burst amplitude and decreased the respiratory frequency, while normocapnic acidic Krebs solution increased the respiratory frequency with no change in burst amplitude. 6. These results show that respiratory responses to changes in CO2 and pH depend upon the sites of action. While a CO2 increase or a pH decrease affected the respiratory frequency in the deep brainstem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…A hypercapnic response, manifest as increased frequency of lung ventilation, is well established for air-breathing lower vertebrates: turtles (17), toads (2, 32), lungfish (29), and gar (42). CO 2 -pH sensitivity of isolated brain stems has been shown for mammals (25,39) and turtles (18) as well as bullfrog tadpoles (37) and adult frogs (20). Reported here is further evidence that the isolated bullfrog brain stem is capable of generating a fictive hypercapnic response in all stages of metamorphosis, and this response is predictable and reliable throughout development.…”
Section: Discussionmentioning
confidence: 60%
“…A hypercapnic response, manifest as increased frequency of lung ventilation, is well established for air-breathing lower vertebrates: turtles (17), toads (2, 32), lungfish (29), and gar (42). CO 2 -pH sensitivity of isolated brain stems has been shown for mammals (25,39) and turtles (18) as well as bullfrog tadpoles (37) and adult frogs (20). Reported here is further evidence that the isolated bullfrog brain stem is capable of generating a fictive hypercapnic response in all stages of metamorphosis, and this response is predictable and reliable throughout development.…”
Section: Discussionmentioning
confidence: 60%
“…When the superfusate was made acid by decreasing solution HCO 3 Ϫ content at constant PCO 2 (metabolic acidosis), burst frequency increased, indicating that these superficial chemosensitive neurons respond differently to acidosis induced by increased CO 2 level compared with metabolic acidosis. Denavit-Saubié et al (92) and Morin-Surun et al (234) further showed that when the perfusate was made hypercapnic, thus activating deeper chemosensitive neurons, there was an increase in burst frequency but a decrease in amplitude. The finding that deeper chemosensitive neurons give a different response to hypercapnia than superficial neurons suggests that there are differences in the response of chemosensitive neurons from different regions to the same stimulus.…”
Section: Reduced Preparationsmentioning
confidence: 92%
“…In the first, the brain stem only was removed from an adult guinea pig (92,234). In this preparation, ventilatory output was measured with suction electrodes on the hypoglossal roots (also reflective of respiration).…”
Section: Reduced Preparationsmentioning
confidence: 99%
“…Whereas superfusion with acid solutions at constant PCO 2 generally led to increases in respiratory (phrenic or hypoglossal) motor drive (9,11,35), isohydric hypercapnia was effective in only some preparations (11,35), or completely failed to drive respiratory motor output (9).…”
Section: Intracellular [H ϩ ] As the Adequate Stimulus To Central Chementioning
confidence: 95%